Temperature-sensitive yeast mutants defective in mitochondrial inheritance (The Rockefeller University Press, 1990)
The distribution of mitochondria to daughter cells is an essential feature of mitotic cell growth, yet the molecular mechanisms facilitating this mitochondrial inheritance are unknown. We have isolated mutants of Saccharomyces cerevisiae that are temperature- sensitive for the transfer of mitochondria into a growing bud. Two of these mutants contain single, recessive, nuclear mutations, mdm1 and mdm2, that cause temperature-sensitive growth and aberrant mitochondrial distribution at the nonpermissive temperature. The absence of mitochondria from the buds of mutant cells was confirmed by indirect immunofluorescence microscopy and by transmission electron microscopy. The mdm1 lesion also retards nuclear division and prevents the transfer of nuclei into the buds. Cells containing the mdm2 mutation grown at the nonpermissive temperature sequentially form multiple buds, each receiving a nucleus but no mitochondria. Neither mdm1 or mdm2 affects the transfer of vacuolar material into the buds or causes apparent changes in the tubulin- or actin-based cytoskeletons. The mdm1 and mdm2 mutations are cell-cycle specific, displaying an execution point in late G1 or early S phase.